2016
DOI: 10.1016/j.msea.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the allotropic phase transformation in titanium processed by high-pressure torsion using different rotation speeds

Abstract: An investigation was initiated to examine the effect of rotation speed on the allotropic α to ω-phase transformation in titanium. A grade 2 commercial purity titanium was processed by high-pressure torsion (HPT) at room temperature up to a maximum of 10 turns using a pressure of 5.0 GPa and different rotation speeds from 0.5 to 2 rpm. It is shown that the allotropic phase transformation occurs during HPT at different rotation speeds but the volume fraction of the ω-phase decreases when the rotation speed is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 37 publications
4
19
0
1
Order By: Relevance
“…Nevertheless, this phase was observed in commercially pure Ti as an additional plastic deformation mode comparable to twinning [16,17] after the same experimental procedure. An important parameter governing the α to ω transformation is the role of impurities in Ti, in particular the oxygen content [38] and it seems that this parameter is very important in suppressing the α to ω transformation in the Ti-6Al-4V alloy which contains 6% Al and 4%…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Nevertheless, this phase was observed in commercially pure Ti as an additional plastic deformation mode comparable to twinning [16,17] after the same experimental procedure. An important parameter governing the α to ω transformation is the role of impurities in Ti, in particular the oxygen content [38] and it seems that this parameter is very important in suppressing the α to ω transformation in the Ti-6Al-4V alloy which contains 6% Al and 4%…”
Section: Discussionmentioning
confidence: 74%
“…High-pressure torsion (HPT) is a well-established SPD procedure [11][12][13] and in pure Ti it was established that there may be an α (hcp) to ω (hcp) phase transformation during HPT processing [14][15][16][17]. Similarly, HPT-induced β to ω [18] and α" to ω [19] phase transformations were reported in a Ti-Nb alloy.…”
Section: Introductionmentioning
confidence: 99%
“…The large hydrostatic stress developed during this processing operation prevents cracking and permits processing at room temperature. Thus grain sizes in the range of a few hundreds of nanometers have been reported in CP-Ti processed by HPT [15][16][17][18][19][20][21] . Also, titanium exhibits a phase transformation at high pressures into an hexagonal ω-phase 22,23 .…”
mentioning
confidence: 87%
“…It was reported that the ω-phase is denser despite the less-packed structure and this was attributed to the smaller atomic size 22 . Recent research shows that the ω-phase is formed in CP-Ti processed by HPT 16,17,20,21,24 . The high pressures developed in this process lead to a phase transformation and the imposed torsional strain stabilizes the hexagonal phase upon pressure release.…”
mentioning
confidence: 99%
See 1 more Smart Citation